Evaluating hedge fund performance - Tran, Vinh Quang, 1946- (John Wiley, 2006)
A comprehensive look at hedge fund performance issuesIn Evaluating Hedge Fund Performance, Dr. Vinh Tran gives readers the information they need to construct an efficient hedge fund portfolio based on their own level of knowledge. From evaluating hedge funds to picking the winners, Dr.